New Communities on Eucalypts Grown Outside Australia - Mansfield, Sarah (Frontiers in Plant Science, 2016)
The expansion of eucalypt forestry worldwide has been accompanied by accidental and deliberate introductions of Australian insects associated with eucalypts. Local insect species have also colonised introduced eucalypts in many regions. This situation provides a unique opportunity to observe the development of new insect communities across trophic levels. Here the history of Australian invaders and native colonisers on eucalypts outside Australia is reviewed from the perspective of herbivore guilds: leaf chewers, sap suckers, wood borers, gall formers, termites. Historical patterns of invasion are identified across these guilds. Very few species of Australian leaf chewers, wood borers or termites have become widespread but these guilds are proportionately high in native colonisers. In contrast, sap suckers have multiple invasive species globally with relatively fewer native colonisers. The gall former guild also has several invasive species but so far includes no native colonisers, perhaps due to their tendency to have highly specific host plant associations. Natural enemies of Australian invaders are also members of new eucalypt insect communities, partly through planned biological control programs, but the rate of accidental introductions at higher trophic levels is increasing steadily. At the same time, local natural enemies enter eucalypt communities either to form new associations with Australian invaders or to follow native colonisers into this new habitat. Australian sap suckers have attracted far more new associations than other guilds so far. Native leaf chewers have often been followed by their local natural enemies into eucalypt communities, particularly in Brazil. Generally there are fewer records relating to local natural enemies and their role in new eucalypt communities. The complexity of new eucalypt communities outside Australia is expected to increase in future.